Strategy of Da'wah Communication in Coping Family Problems in Parepare City - Muhammad Qadaruddin; Nur Afiah; Suhartina Suhartina (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2018)
This study aims to find out 1) the forms of problems of family in the millenial era, 2) relations that occur in the family, and 3) the role of Islamic communication in realizing family harmony. This type of research is qualitative research. The technique of collecting data through observation, interviews and documentation. The data analysis technique used in this study is data reduction, data presentation and conclusion drawing. The results showed that (1) the form of family problems in the millennial era that occurred was the intensity of excessive use of gadgets on children and the busyness between husband and wife who both worked, (2) Relationships that occur are relations between husband, wife and children, and relationship between husband and wife. Informants 1 and 3 have similarities in functional components in the family. on the transactional component in the family, the first and second informants develop the component. The first informant developed a pattern of behavior in the relationship between husband and wife and children. The second informant, the development of behavior is more on the relationship of husband and wife. (3) The role of Islamic communication in realizing: openness, support, positive feelings, empathy, and similarity.Penelitian ini bertujuan untuk mengetahui 1) bentuk-bentuk problematika keluarga di era millenial, 2) relasi yang terjadi dalam keluarga, dan 3) peran komunikasi Islam dalam mewujudkan keharmonisan keluarga. Jenis penelitian ini adalah penelitian kualitatif. Teknik pengumpulan data melalui observasi, wawancara dan dokumentasi. Teknik analisis data yang digunakan dalam penelitian ini adalah reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa (1) bentuk problematika keluarga di era millenia yang terjadi adalah intensitas penggunaan gadget yang berlebihan pada anak dan kesibukan antara suami dan istri yang sama-sama bekerja, (2) Relasi yang terjadi adalah relasi suami, istri dan anak, serta relasi antara suami dan istri. Informan 1 dan 3 memiliki kesamaan pada komponen fungsional dalam keluarga. pada komponen transaksional dalam keluarga, informan pertama dan kedua mengembangkan komponen tersebut. Informan pertama mengembangkan pola perilaku pada relasi suami istri dan anak. Sedangkan pada informan kedua, pengembangan perilaku lebih pada relasi suami istri. (3) Peran komunikasi Islam dalam mewujudkan keterbukaan, dukungan, perasaan positif, empati, dan kesamaan.